Analysis of energy performance of a photoelectric battery to determine the optimal tilting angle - Shokir N. Abilfayziyev; Khushbok U. Panjiyev; Bozorbek M. Botirov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: the optimal tilt angle of photovoltaic cells (PV modules) plays an important role in energy production. It is often observed that PV modules are installed in accordance with the natural slopes of roofs, without paying attention to the optimal angle to maximize the use of sunlight. The efficiency of PV models installed at the wrong angle decreases, which reduces the amount of energy production. Therefore, installing PV modules, especially photovoltaic stations, at the optimal angle is important for PV systems. This article presents an analysis of the electrical parameters of a 550W PV module at various tilt angles in a stationary state before installing a 100kW solar photovoltaic station (SPS). Aim: determining the optimal tilt angle of PV modules and their energy performance in real conditions in the city of Termez, a southern region of the republic. Methods: since the photovoltaic stations are installed “stationary”, the “stationary” method of measuring the electrical parameters of the PVs was also used in the experiment. Results: various tilt angles were tested to determine the optimal tilt angle of PV modules in the southern region of the republic. In this case, the best angle for installing a PV module at a constant (stationary) angle for the city of Termez was angles from 340 to 380. As for seasonal installation angles, it is recommended to increase the recommended angle for the winter season by 100-120 degrees compared to the angle (from 340 to 380) and reduce it by the same number of degrees for the summer season. The optimal tilt angle and direction of the solar panel depend on the month of the year and the geographical coordinates of the studied location.